Rationale set of indicators and prioritize relevant to assess competitive activity of hockey players of high qualification of different roles - Mikhnov, A. P. (Physical Education of Students, 2015)
Purpose: organize technical and tactical actions and determine their priority importance for high-end players of different roles. Establish their priority importance for the success of competitive activity hockey with the game roles. Material : the study involved 54 experts on hockey coaches and players of high class. The significance of technical and tactical actions evaluated for players of different roles. Results : systematic account of technical and tactical actions of athletes and prioritize them to assess the significance of competitive activity. Three groups of technical and tactical actions: 1) active attacks; 2) - active safety; 3) - organizational and maneuvering. Set priorities for technical and tactical actions for players of different roles. Conclusions : the proposed technical and tactical actions can be recommended for the evaluation of the effectiveness of competitive activity players. In the process of estimating the action game players need to consider their role playing. Identification of priority in the implementation of technical and tactical actions in the game can be used in integrated assessment of actions players different roles.